Determinants of Stock Returns: The Moderating Role of Company Size (Empirical Study of Property and Real Estate Companies Listed on the Indonesian Stock Exchange 2019-2023) - Lutfi, Mustafa; Endri, Endri (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This research aims to test and analyse the influence of return on assets (ROA), net profit margin (NPM), debt-to-equity ratio (DER), and inflation on property and real estate company stock returns in 2019–2023. The research approach uses the method of quantitative research with panel data regression models using Eviews 12.0 software. The population in this research is property sector companies registered on the IDX in 2019–2023. The sampling technique used is purposive sampling. The research results show that there is no significant influence between return on assets (ROA) and stock returns; there is a positive but not significant relationship between net profit margin (NPM) and stock returns; there is no significant relationship between debt-to-equity ratio and stock returns; and inflation has a significant influence on stock returns of property and real estate companies in 2019–2023.